Feasible Region Analysis of Penetration Level of PV in Active Distribution Networks - Hua, Shenghui; Zhang, Mingze; Xing, Xin; Wang, Jian (2023 3rd Power System and Green Energy Conference (PSGEC), 2023)
With the promotion of new energy power system in China, large-scale connection of distributed photovoltaic (PV) has brought uncertain risks to the distribution network. Energy storage (ES) can support a high penetration rate of renewable energy integrated into the distribution network due to its flexible control characteristics. In this paper, the proposed method based on the multi-parameter programming method can visualize the feasible region boundary of PV access capacity with full consideration of the coupling effects among different access nodes. Firstly, the typical scenarios of PV are obtained by clustering. Then, a method is proposed to describe the feasible region considering the operation constraints of distribution network and ES operation constraints, which takes the PV access capacity of different nodes as the planning parameter. Finally, the effectiveness of the feasible region acquisition method is verified through the simulation of IEEE-33 bus system, and the influence of ES on the feasible region of PV capacity is analyzed.